Computational Identification of MicroRNAs from the Expressed Sequence Tags of Toxic Dinoflagellate Alexandrium Tamarense. (January 2013) - Gao, Dahai; Qiu, Limei; Hou, Zhanhui; Zhang, Qingchun; Wu, Jianmin; Gao, Qiang; Song, Linsheng
Micro ribonucleic acids (miRNAs) represent a class of small noncoding RNAs that play important roles in multiple biological processes by degrading targeted mRNAs or by repressing mRNA translation. In the case of algal lineages, especially dinoflagellates, knowledge regarding the miRNA system is still limited and its regulatory role remains unclear. In the present study, a computational approach was employed to screen miRNAs from the expressed sequence tags (ESTs) of Alexandrium tamarense . A total of 18 potential miRNAs were identified according to a range of filtering criteria. In addition, unique evolutionary features, such as miRNA gene duplication and sequence similarity to metazoan miRNAs, implied that the miRNA system in dinoflagellates is complex. Moreover, based on these 18 miRNA sequences, 42 potential target genes showing diverse functions in regulating growth and development were predicted in Thalassiosira pseudonana and Phaeodactylum tricornutum . Taken together, our data suggest the existence of miRNAs in dinoflagellates and provide clues for further functional studies on these predicted miRNAs.